Stabilization of rational nonlinear discrete-time systems by state feedback and static output feedback. (September 2022) - Reis, Gabriela L.; Araújo, Rodrigo F.; Torres, Leonardo A.B.; Palhares, Reinaldo M.
Abstract: The design of State Feedback (SF) and Static Output Feedback (SOF) controllers for nonlinear discrete-time systems subject to time-varying parameters is discussed in the context of Difference-Algebraic Representations (DAR) and parameter-dependent Lyapunov functions applied to obtain convex conditions in the form of Linear Matrix Inequalities (LMI). The proposed conditions guarantee the system robust stabilization and provide an estimate of the Domain-of-Attraction (DoA). Firstly, a novel strategy for gain-scheduled SF control is proposed incorporating information on the system's nonlinearities to compute the control action. Secondly, a new gain-scheduled SOF control design solution is derived, without structural constraints imposed on the output matrix and without making use of iterative algorithms, unlike most approaches in the current literature. Finally, numerical examples illustrate the proposed methodology's potential.